Pseudoacromegaly - a challenging entity in the endocrine clinic: a systematic review - Marques, Pedro (2024)
Objective: Pseudoacromegaly encompasses conditions with features of acromegaly/ gigantism, but no growth hormone (GH) or insulin‐like growth factor‐1 (IGF‐1) excess. We aimed to review published pseudoacromegaly cases evaluated due to clinical suspicion of acromegaly. Design/Patients: PubMed/Medline search was conducted to identify reported pseudoacromegaly cases, which were systematically reviewed to ensure they met eligibility criteria: (1) presentation suggestive of acromegaly; (2) acromegaly excluded based on normal GH, IGF‐1 and/or GH suppression on oral glucose tolerance test (OGTT‐GH); (3) diagnosis of the pseudoacromegaly condition was established. Data were retrieved from each case and analysed collectively. Results: Of 76 cases, 47 were males, mean ages at presentation and at first acromegaloid symptoms were 28 ± 16 and 17 ± 10 years, respectively. Most common conditions were pachydermoperiostosis (47%) and insulin‐mediated pseudoacromegaly (IMP) (24%). Acromegaloid facies (75%) and acral enlargement (80%) were the most common features. Measurement of random GH was reported in 65%, IGF‐1 in 79%, OGTT‐GH in 51%. GH excess was more frequently excluded based on two tests (53%). Magnetic resonance imaging (MRI) was performed in 30 patients, with pituitary adenoma or hyperplasia being reported in eight and three patients, respectively. Investigations differed between cases managed by endocrine and non‐endocrine specialists, the former requesting more often IGF‐1, OGTT‐GH and pituitary MRI. Conclusions: Pseudoacromegaly is a challenging entity that may be encountered by endocrinologists. Pachydermoperiostosis and IMP are the conditions most often mimicking acromegaly. Adequate assessment of GH/IGF‐1 is crucial to exclude acromegaly, which may be better performed by endocrinologists. Pituitary incidentalomas are common and require careful judgement to prevent unnecessary pituitary surgery.